The scope of Shariah audit in Islamic financial institutions (IFIs): A comparative study of Malaysia and Indonesia / Nawal Kasim … [et al.] - Kasim, Nawal; Mohd Sanusi, Zuraidah; Handoyo, Sigit; Mutamimah, Tatik (Research Management Institute (RMI), 2012)
Drastic development of Islamic financial institutions globally may lead to new expectations of and requirements for accountability, which in turn lead to new demands on the audit function of the institutions. The prohibition of interest and the aspiration of Muslims to make this prohibition a practical reality in their economies, has led to the establishment of a number of Islamic financial institutions around the world. Religious or Shariah audit evolved in parallel to the development of these institutions The study examines the scope of the current practice of auditing in Islamic financial institutions using questionnaires survey in Indonesia and Malaysia. It further examines if IFIs manage to strengthen their social accountability dimension towards their social objectives via their auditing function. This is imperative as the IFIs are expected not only to avoid transactions on the basis of interest but also to participate actively in achieving the goals and objectives of an Islamic economy. The research reports findings on the need to extend the scope of Shariah audit to a broader sense to be in line with the socio-economic objectives of the Islamic law. It is also found that IFIs are facing with serious challenges from the well-established conventional financial system whereby Shariah auditors may face with immense challenges from the policy makers and top management who are progressive thinkers of diverse faiths and practices. Above all, lacking in a comprehensive Shariah audit framework and expertise add to the problem of implementation of Shariah audit in IFIs, Finally, it offers recommendations to bridge the gap between the theory and practice.